The strophic structure of the eulogy of Ephesians 1:3-14 - Barkhuizen, J. H. (Hervormde teologiese studies, 1990)
Since Eduard Norden’s (1913) statement concerning the awkward length and construction of Ephesians 1:3-14, a flood of studies have been devoted to the analysis of this Greek sentence. In this paper I have firstly given an overview of those studies representative of the structure of the eulogy of Ephesians 1:3-14, and secondly presented a new reconstruction of this passage based on principles of form and content.